Strigolactone signaling in the endodermis is sufficient to restore root responses and involves SHORT HYPOCOTYL 2 (SHY2) activity. Issue 3 (21st February 2013) - Koren, Dikla; Resnick, Nathalie; Gati, Einav Mayzlish; Belausov, Eduard; Weininger, Smadar; Kapulnik, Yoram; Koltai, Hinanit
Summary Strigolactones (SLs) are plant hormones and regulators of root development, including lateral root (LR) formation, root hair (RH) elongation and meristem cell number, in a MORE AXILLARY GROWTH 2 (MAX2)‐dependent way. However, whether SL signaling is acting cell‐autonomously or in a non‐cell‐autonomous way in roots is unclear. We analyzed root phenotype, hormonal responses and gene expression in multiple lines of Arabidopsis thaliana max2‐1 mutants expressing MAX2 under various tissue‐specific promoters and shy2 mutants. The results demonstrate for the first time that expression of MAX2 under the SCARECROW (SCR) promoter, expressed mainly in the root endodermis, is sufficient to confer SL sensitivity in the root for RH, LR and meristem cell number. Moreover, loss of function mutation of SHORT HYPOCOTYL 2 (SHY2), a key component in auxin and cytokinin regulation of meristem size, has been found to be insensitive to SLs in relation to LR formation and meristem cell number. Endodermal SL signaling, mediated by MAX2, is sufficient to confer SL sensitivity in root, and SHY2 may participate in SL signaling to regulate meristem size and LR formation. These SL signaling pathways thus may act through modulation of auxin flux in the root tip, and may indicate a root‐specific, yet non‐cell‐autonomous regulatory mode of action.